Study of the Trilinear Neighborhood Model of Process of Formation of Temperature’s Coiling Hot-rolled Strip - A.M. Shmyrin; A.G. Yurtsev; A.M. Korneev; L.S. Abdullakh (International Journal of Electrical and Computer Engineering (IJECE), 2016)
The paper considers trilinear neighborhood model of process of formation of temperature’s coiling hot-rolled strip, where the parameters are the state, control and information. The methods of determining the composition of extremums of the general parametric operation are presented. Extremums’ condition for the existence, which has been tested on a concrete example, is obtained. The assumption about the area in which it is impossible to say with certainty about the system’s stability is stated. The hypothesis about the condition of the loss of the position of stable equilibrium of the system and the transition to a new state.